A cultivation-independent PCR-RFLP assay targeting oprF gene for detection and identification of Pseudomonas spp. in samples from fibrocystic paediatric patients - Lagares, Antonio (2015)
Species-specific genetic markers are crucial to develop faithful and sensitive molecular methods for the detection and identification of Pseudomonas aeruginosa (Pa). We have previously set up a PCR-RFLP protocol targeting oprF, the gene encoding the genus-specific outer membrane porin F, whose strong conservation and marked sequence diversity allowed detection and differentiation of environmental isolates (Agaras et al., 2012). Here, we evaluated the ability of the PCR-RFLP assay to genotype clinical isolates previously identified as Pa by conventional microbiological methods within a collection of 62 presumptive Pa isolates from different paediatric clinical samples and different sections of the Hospital de Niños ?Sor María Ludovica? from La Plata, Argentina. All isolates, but one, gave an oprF amplicon consistent with that from reference Pa strains. The sequence of the smaller-sized amplicon revealed that the isolate was in fact a P. mendocina strain. The oprF RFLP pattern generated with TaqI or HaeIII nucleases matched those of reference Pa strains for 59 isolates (96%). The other two Pa isolates (4%) revealed a different RFLP pattern based on HaeIII digestion, although oprF sequencing confirmed that Pa identification was correct. We next tested the effectiveness of the PCR-RFLP to detect pseudomonads on clinical samples of paediatric fibrocystic patients directly without sample cultivation. The expected amplicon and its cognate RFLP profile were obtained for all samples in which Pa was previously detected by cultivation-dependent methods. Altogether, these results provide the basis for the application of the oprF PCR-RFLP protocol to directly detect and identify Pa and other non-Pa pseudomonads in fibrocystic clinical samples.